DEVELOPMENT OF VALUE ADDED BISCUIT FOR PEOPLE LIVING WITH HUMAN IMMUNO DEFICIENCY VIRUS - DEVIKA.I; THAHIRA BANU.A (International Journal of Pharma and Bio Sciences, 2016)
The study was undertaken to formulate a biscuit incorporated with whey protein and banana flour to find its suitability for PLWHIV. The ingredients namely white flour (Maida), wheat, whey protein banana, carrot, sweet potato and powdered nuts were collected based on each of the ingredients functional properties for development of the biscuit. Four variations of the biscuit with a difference in proportion of ingredients were selected and coded as A, B, C and D. Among the four, variations C had the highest overall acceptability. Thus variation C was taken for analysis of the nutrients namely carbohydrate, protein, and fat, fractions of fat, selenium, zinc, iron, beta carotene and vitamin C using standard procedures. The shelf life of the biscuit was also evaluated on the 30th day of storage. The findings of the study were very promising in terms of the nutrients present in the biscuits. The biscuit had carbohydrate-65g, protein-13g, fat-22g, MUFA-1.02g, PUFA-2.53g, selenium-8.9µg, zinc-3.37mg, vitamin C-9.6mg, betacarotene-1220 mcg and iron -20mg per 100gm of the product. Thus from the study it is found that the whey protein, sweet potato and banana flour incorporated biscuit has substantial quantity of protein, PUFA, vitamin C and other nutrients required for a PLWHIV.